The Alternative Sigma Factor SigH Regulates Major Components of Oxidative and Heat Stress Responses in Mycobacterium tuberculosis - Raman, Sahadevan (American Society for Microbiology, 2001)
Mycobacterium tuberculosis is a specialized intracellular pathogen that must regulate gene expression to overcome stresses produced by host defenses during infection. SigH is an alternative sigma factor that we have previously shown plays a role in the response to stress of the saprophyte Mycobacterium smegmatis. In this work we investigated the role of sigH in the M. tuberculosis response to heat and oxidative stress. We determined that a M. tuberculosis sigH mutant is more susceptible to oxidative stresses and that the inducible expression of the thioredoxin reductase/thioredoxin genes trxB2/trxC and a gene of unknown function, Rv2466c, is regulated by sigH via expression from promoters directly recognized by SigH. We also determined that the sigH mutant is more susceptible to heat stress and that inducible expression of the heat shock genes dnaK and clpB is positively regulated by sigH. The induction of these heat shock gene promoters but not of other SigH-dependent promoters was markedly greater in response to heat versus oxidative stress, consistent with their additional regulation by a heat-labile repressor. To further understand the role of sigH in the M. tuberculosis stress response, we investigated the regulation of the stress-responsive sigma factor genes sigE and sigB. We determined that inducible expression of sigE is regulated by sigH and that basal and inducible expression of sigB is dependent on sigE and sigH. These data indicate that sigH plays a central role in a network that regulates heat and oxidative-stress responses that are likely to be important in M. tuberculosis pathogenesis.